DIFFICULTY ANALYSIS OF PHYSICS STUDENTS IN LEARNING ONLINE DURING PANDEMIC COVID-19 - Fauza, Naila; Ernidawati, Ernidawati; Syaflita, Dina (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2020)
Â COVID-19 attacked Wuhan city in December 2019 where the number of cases increased rapidly, but the clinical information of infected patients was limited. One of the negative effects related is the education sector. COVID-19 also changed the learning model drastically, all learning activities were carried out online. This causes students difficulties in learning. The purpose of the research was to analyze the difficulty factors of physics education students in distance learning during the COVID-19 pandemic. This type of research is descriptive research. Data collection techniques using a questionnaire. Research subjects were 80 students from Physics education at FKIP Riau University. The results of research online learning difficulties come from two factors, namely external and internal factors. External factors include non-current internet networks and very many student assignments. Internal factors related to students' learning difficulties, students generally have difficulty communicating and discussing both fellow students and with lecturers, misconceptions occur, difficulties in summarizing the material, and eye discomfort due to cellphone and laptop radiation.